The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1163/156856103321645194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atmospheric pressure helium/air plasma treatment on adhesion and mechanical properties of aramid fibers

Abstract: In order to investigate the effect of atmospheric pressure plasmas on adhesion between aramid bers and epoxy, aramid bers were treated with atmospheric pressure helium/ air for 15, 30 and 60 s on a capacitively-coupleddevice at a frequency of 5.0 kHz and He outlet pressure of 3.43 kPa. SEM analysis at 10 000£ magni cation showed no signi cant surface morphological change resulted from the plasma treatments. XPS analysis showed a decrease in carbon content and an increase in oxygen content. Deconvolution analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 38 publications
4
29
0
1
Order By: Relevance
“…The tensile strength values of the plasma treated fibers often tended to be lower, which may be due to the introduction of cracks and pits on the fiber surface by plasma etching after long exposure to plasma. However, it has been shown that fiber strength could also be increased due to elimination of small defects by plasma etching [32]. In the current study, the reaction between ethanol and plasma could consume substantial amount of energy and thus reduce plasma etching effect on the ethanol pretreated fibers.…”
Section: Interfacial Shear Strengthmentioning
confidence: 79%
“…The tensile strength values of the plasma treated fibers often tended to be lower, which may be due to the introduction of cracks and pits on the fiber surface by plasma etching after long exposure to plasma. However, it has been shown that fiber strength could also be increased due to elimination of small defects by plasma etching [32]. In the current study, the reaction between ethanol and plasma could consume substantial amount of energy and thus reduce plasma etching effect on the ethanol pretreated fibers.…”
Section: Interfacial Shear Strengthmentioning
confidence: 79%
“…The important decrease in the contact angle in the PLA samples treated with air atmospheric plasma and the wettability increase was mainly due to surface activation and roughness change. [30][31][32][33][34][35] ) with a surface energy of 37 mJ m -2 , it is possible triple the strength of the PLA-PLA adhesion joints. For higher nozzle-substrate distances, the atmospheric plasma treatment was less effective.…”
Section: Tablementioning
confidence: 99%
“…Plasma consists of highly active charged species; electrons, ions, and radicals, and can create highly unusual environments to interact with material surfaces. Plasma treatment of polymer materials results in surface modification through various functionalizations such as etching, deposition, chain scission, and cross-linking [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%